ЗЕЛЕНЫЙ СИНТЕЗ, СТРУКТУРА И ФИЗИКО-ХИМИЧЕСКИЕ СВОЙСТВАНАНОМАТЕРИАЛА LaFeO₃ НА ОСНОВЕ АЛКОГОЛЬНОГО ЭКСТРАКТА ALLOCHRUSA GYPSOPHILOIDES (Universal xalqaro ilmiy jurnal, 2026)
In this work, LaFeO₃ perovskite nanomaterial was synthesized via anenvironmentally friendly green synthesis route using the alcoholic extract of Allochrusagypsophiloides. The structural, functional, and elemental characteristics of the synthesized samplewere comprehensively investigated by X-ray diffraction (XRD), Fourier transform infraredspectroscopy (FTIR), and energy-dispersive X-ray spectroscopy (EDX), respectively. The XRDresults confirmed the formation of a single-phase orthorhombic perovskite structure without anydetectable impurities. FTIR spectra revealed characteristic absorption bands corresponding to Fe–Oand La–O bonds. Elemental analysis indicated that the mass percentages of La₂O₃ and Fe₂O₃ were47.8% and 52.2%, respectively, demonstrating good stoichiometric agreement. The obtained resultsconfirm the effectiveness, simplicity, and environmental sustainability of the green synthesis approachfor producing high-purity LaFeO₃ nanomaterials with promising catalytic and photocatalyticapplications
Keywords: LaFeO₃; XRD; FTIR